Comparison of Short Tandem Repeat Loci D2S1338 and D18S51 in the Populations of the Republic of Srpska and the Autonomous Province of Vojvodina - Samardžić, Branka; Karan, Željko; Obradović, Zoran; Došen, Dijana (Scripta Medica, 2021)
Introduction: Numerous human migrations between Bosnia and Herzegovina and Serbia’s northern province of Vojvodina have led to the increased mixing of these population's genetic pool, leading to a reduction in genetic differences. The question is whether there are now genetic differences between the mentioned populations. Methods: Short Tandem Repeat (STR) loci D2S1338 and D18S51 were used in this paper to compare the diversity of alleles and genotypes between the populations of Vojvodina and one of the two Bosnia’s entities, the Republic of Srpska (RS). Three hundred ninety unrelated persons, 140 persons from the RS and 260 from Vojvodina, were analysed. The PowerPlex ESX16 System commercial kit was used for profiling persons from the territory of the RS and the AmpF/STR Identifiler commercial kit for persons from Vojvodina. The Mann-Whitney U-test was used for statistical analysis.Results: Data analysis concluded a significant deviation in the allele frequency of the D18S51 locus where p = 0.021. There was no statistically significant deviation in the D2S1338 locus allele frequency between these two populations. It was also found that there is a statistically significant deviation in the genotype frequencies of these two populations for the analysed genetic markers. Conclusion: This study confirms the existence of a significant deviation of allelic frequency for the D18S51 gene locus and a significant deviation of both gene markers frequency of genotypes.
Keywords: Human genome; Alleles; Microsatellite repeats; Population genetics